Formulation and Evaluation of Bendamustine Loaded Polymeric Nanoparticle - Telsang, Mallikarjun; D, Pradeep; B, Wilson; Tamreen, Vasia; Sadik, Shaik; Habeebuddin, Mohammed; Asif, Afzal Haq; Asdaq, Mohammed Basheeruddin; Nagaraja, Sree Harsha; Noor, Syed Dawood (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Bendamustine-loaded albumin nanoparticles were prepared using different concentrations of Bovine Serum Albumin (BSA) with the goal of delivering the medication to particular cancer cells. Materials and Procedures: The nanoparticles were prepared using simple coacervation technique with increasing concentrations of BSA. The nanoparticles were characterized for process yield, particle size, surface morphology, drug loading capacity (%), particle size distribution (Polydispersity index), in-vitro drug release. The drug release kinetics were studies using different dissolution models. The drug loading capacity of the produced nanoparticles varied from 10.4% to 19%. Formulation (F1) had a mean particle size of approximately 122.4 nm and polydispersivity index of 0.432 across the different compositions. Bendamustine nanoparticles exhibit sustained drug release with almost 51.8% bendamustine released in one day. The drug release kinetics follows Korsmeyer-Peppas model with a Fickian drug release mechanism. The Bendamustine nanoparticles were found to be stable for a month at 40±5C and 75±5% relative humidity. Conclusion: Bendamustine loaded BSA nanoparticles were developed which were found to exhibit a sustained drug release profile. Albumin based Bendamustine nanoparticles have the potential to be explored further for the better management of the cancer chemotherapy with reduced side effects.
Keywords: Nanoparticles; Bendamustine; Cancer; Bovine serum albumin; Bendamustine; albumin; Release kinetics; Surface morphology